Integrated Proteomics and Metabolomics Reveal Molecular Differences and Regulatory Mechanisms Underlying Sturgeon Egg Quality - Zhou Zhou; Xianbo Zhang; Jinli Hu; Feng Chen; Shenghan Lue; Qinglan Zhou; Ning Qin (Fishes, 2026)
Integrated proteomics and untargeted metabolomics were employed to systematically characterize molecular differences between Acipenser schrenckii embryos with normal versus abnormal 24 h post-fertilization (24 hpf), which were classified as high-quality (HQ) and poor-quality (PQ) groups. Among 1636 proteins and 1102 metabolites, 220 differentially expressed proteins (DEPs) and 365 differential metabolites (DMs) were identified. Functional enrichment demonstrated that HQ samples were predominantly enriched in pathways associated with amino acid biosynthesis, glycolysis/tricarboxylic acid cycle, nucleotide metabolism, and mRNA surveillance, which collectively supported material accumulation, energy supply, and embryonic developmental competence. In contrast, PQ samples were mainly enriched in oxidative phosphorylation, mitochondrial stress response, arachidonic acid metabolism, and immune and inflammatory signaling pathways, indicating severe lipid metabolic disorders and excessive oxidative stress. Spearman correlation analysis identified L-pyroglutamic acid and ascorbic acid as core correlated metabolic hubs associated with high-quality eggs, while natamycin and tetrahydrocorticosterone were correlated characteristic metabolic signatures enriched in deteriorated eggs. Key protein nodes showing strong correlations with 24 hpf developmental phenotypes included GAPDH, glutathione S-transferase, and CYP450 2E1. Collectively, this study reveals divergent correlated molecular profiles linked to normal versus abnormal 24 hpf development and screens correlative multi-omics candidate signatures for distinguishing well-developed and deteriorated oocytes.